The Role of Central Command in the Increase in Muscle Sympathetic Nerve Activity to Contracting Muscle During High Intensity Isometric Exercise - Boulton, Daniel; Taylor, Chloe E.; Green, Simon; Macefield, Vaughan G. (Frontiers in Neuroscience, 2021)
We previously demonstrated that muscle sympathetic nerve activity (MSNA) increases to contracting muscle as well as to non-contracting muscle, but this was only assessed during isometric exercise at ~10% of maximum voluntary contraction (MVC). Moreover, we had also shown that electrically-evoked contractions at ~10% MVC did not produce increases in MSNA to the contracting muscle, suggesting that central command is responsible for the increase in vasoconstrictor drive. Here we tested the hypothesis that central command is also primarily responsible for the increase in MSNA to contracting muscle during high-intensity exercise, and that the metaboreflex does not contribute. MSNA was recorded continuously via a tungsten microelectrode inserted percutaneously into the right common peroneal nerve in 12 participants, performing isometric dorsiflexion of the right ankle at 10, 20, 30, 40 and 50% MVC for two minutes. Contractions were immediately followed by six minutes of post-exercise ischemia (PEI); six minutes of recovery separated contractions. Cross-correlation analysis was performed between the negative-going sympathetic spikes of the raw neurogram and the ECG. MSNA increased as contraction intensity increased, reaching mean values (± SD) of 207 ± 210 spikes/min at 10% MVC (P=0.04), 270 ± 189 spikes/min at 20% MVC (P<0.01), 538 ± 329 spikes/min at 30% MVC (P<0.01), 816 ± 551 spikes/min at 40% MVC (P<0.01) and 1097 ± 782 spikes/min at 50% MVC (P<0.01). Mean arterial pressure also increased in an intensity-dependent manner from 76 ± 3 mmHg at rest to 90 ± 6 mmHg (P<0.01) during contractions of 50 % MVC. At all contraction intensities, blood pressure remained elevated during PEI, but MSNA returned to pre-contraction levels, indicating that the metaboreflex does not contribute to the increase in MSNA to contracting muscle even at these high contraction intensities, which is primarily brought about by central command.